Vitamins Mediate Immunological Homeostasis and Diseases at the Surface of the Body - Kunisawa, Jun; Kiyono, Hiroshi (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2015)
The host immune system is regulated not only by endogenous factors, such as cytokines and chemokines, but also by exogenous factors, such as commensal bacteria and dietary materials. Vitamins are vital nutrients that are mainly derived from the diet and commensal bacteria. Accumulating evidence has revealed specific functions of vitamins in the control of host immunity. In agreement with their vital roles in the appropriate maintenance of immunity, excessive or insufficient intake of vitamins leads to the development of immune diseases or susceptibility to infection. In this review, we focus on the diverse but specific immunologic functions of vitamins in regulating host immune responses and their association with immune and infectious diseases.
Keywords: inflammation